1996
DOI: 10.1021/ma951344q
|View full text |Cite
|
Sign up to set email alerts
|

Chain Stiffness and Excluded-Volume Effects in Dilute Polymer Solutions:  Cellulose Tris[(3,5-Dimethylphenyl)carbamate]

Abstract: Nineteen fractions of cellulose tris[(3,5-dimethylphenyl)carbamate] (CTDC) ranging in weight-average molecular weight M w from 2.5 × 104 to 7.5 × 106 have been studied by static light scattering, sedimentation equilibrium, and viscometry in 1-methyl-2-pyrrolidone at 25 °C. Since this cellulose derivative exhibits pronounced optical anisotropy, light-scattering data are corrected for the anisotropy effect on the basis of Nagai theory for the Kratky−Porod (KP) wormlike chain with cylindrically symmetric polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Thus, it is a clear advantage of our model calculations that via Eqs. (20), (21) accurate direct estimates of ℓ p are possible, unlike in experiment. These estimates for ℓ p are tabulated in Ref.…”
Section: A Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is a clear advantage of our model calculations that via Eqs. (20), (21) accurate direct estimates of ℓ p are possible, unlike in experiment. These estimates for ℓ p are tabulated in Ref.…”
Section: A Definitionsmentioning
confidence: 99%
“…In view of an apparent conflict of the estimate [12] n * K = 50 with the Yamakawa-Stockmayer-Shimata theory [16][17][18][19] for worm-like chains the result n * K = 50 was considered as a very fundamental problem [20,21]. However, Tsuboi et al [21] confirmed this estimate for another stiff polymer and concluded that the result n * K = 50 is compatible with the theory. We also note that in d = 2 there occurs a single crossover from rods to self-avoiding walks, any regime of Gaussian-like behavior is completely absent [13,22].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we have investigated dilute-solution behavior and liquid crystal formation of this cellulose derivative in 1-methyl-2-pyrrolidone (or N-methyl-2-pyrrolidone, NMP) by light scattering, sedimentation equilibrium, viscometry, and polarized microscopy (Refs. [5][6][7][8], and analyzed the experimental results on the basis of the Kratky-Porod wormlike chain (Ref. 9) with or without excluded volume.…”
Section: Introductionmentioning
confidence: 99%
“…To make our analysis more quantitative than in the earlier work by Norisuye and Fujita, we here confine ourselves to polymers whose (S 2 ) or [17] data show both unperturbed and perturbed behaviors in the molecular weight range studied. They are CTDC in NMP, 13 • 14 sodium salt of hyaluronic acid (Na-HA) in 0.2 and 0.5 M aqueous sodium chloride/ 5 -1 7 and poly(l-phenyl-1-propyne) (PPP) in toluene/ 8 in addition to PHIC in hexane. 6 No polyelectrolyte in aqueous solution of low ionic strength is included.…”
mentioning
confidence: 99%